The expression of IL10RA in colorectal cancer and its correlation with the proliferation index and the clinical stage of the disease. (October 2018) - Zadka, Łukasz; Kulus, Michał J.; Kurnol, Krzysztof; Piotrowska, Aleksandra; Glatzel-Plucińska, Natalia; Jurek, Tomasz; Czuba, Magdalena; Nowak, Aleksandra; Chabowski, Mariusz; Janczak, Dariusz; Dzięgiel, Piotr
Graphical abstract: Highlights: There is a correlation between IL10RA and Ki67 proliferation index. There is a negative correlation between IL10RA and the CRC clinical stage. The IL10RA expression is higher in healthy surgical margins than in the tumor itself. The manual IRS approach yields similar results of protein expression to these of digital image analysis. Abstract: Introduction: Despite the widely described role of IL10 in immune response regulation during carcinogenesis, there is no established model describing the role of its receptor. The aim of this study is to elucidate the relationship between the subunit alpha of IL10 receptor (IL10RA) in the pathogenesis of colorectal cancer (CRC). Methods: The study was conducted on archived paraffin blocks of 125 CRC patients, from which tissue microarrays (TMA) were made. These were subsequently used for immunohistochemistry to assess the expression of IL10RA, IL10, phosphorylated STAT3 (pSTAT3) and the Ki67 proliferation index. The intensity of both reactions was assessed by independent researchers using two approaches: digital image analysis and the Remmele and Stegner score (IRS). To assess the possible correlations between the two investigated markers and the clinical stage of CRC, the Pearson correlation coefficient was calculated. The expression of aforementioned proteins was assessed in tumor samples, healthy surgical margins and healthy control samples, obtained from cadavers during autopsy from the Department of Forensic Medicine. Statistical analysis was conducted using Statistica ver. 13.05 software. Results: The final analysis included 105 CRC patients with complete clinical and pathological data, for whom the expressions of IL10RA, IL10, pSTAT3 and Ki67 were assessed using two independent methods. There was a positive correlation between the IL10RA expression and Ki-67 proliferation index (R = 0.63, p < 0.001) and a negative correlation between the IL10RA expression and the clinical stage of CRC (R = −0.21, p = 0.022). IL10RA correlated positively with pSTAT3 and IL10 in neoplastic tissue and tumor margin (with p < 0.01 for all correlations). We also observed a significantly higher expression of IL10RA in healthy surgical margins when compared to the actual tumor (p = 0.023, the paired t -test). The expression of IL10 was significantly higher in tumors than in healthy intestinal endothelium from control group. Conclusions: The correlations between the expression of IL10RA and the proliferation index or the clinical stage of CRC seem to confirm the importance of IL10RA in the pathogenesis of CRC. The higher expression of IL10RA in healthy surgical margins than in the tumor itself may suggest that IL10RA plays a role in regulating immune response to the neoplasm.